Religion in American life : a short history - Butler, Jon, 1940-; Wacker, Grant, 1945-; Balmer, Randall Herbert (Oxford ; New York : Oxford University Press, 2011)
"This new edition of Religion in American Life, written by three of the country's most eminent historians of religion, offers a superb overview that spans four centuries, illuminating the rich spiritual heritage central to nearly every event in our nation's history. Beginning with the state of religious affairs in both the Old and New Worlds on the eve of colonization and continuing through to the present, the book covers all the major American religious groups, from Protestants, Jews, and Catholics to Muslims, Hindus, Mormons, Buddhists, and New Age believers. Revised and updated, the book includes expanded treatment of religion during the Great Depression, of the religious influences on the civil rights movement, and of utopian groups in the 19th century, and it now covers the role of religion during the 2008 presidential election, observing how completely religion has entered American politics." -- Publisher's description.
Religion in colonial America / Jon Butler. Worlds old and new ; Religion and missions in New Spain and New France ; Religion and in England's first colonies ; The flowering of religious diversity ; African and American Indian religion ; Religion and American Revolution -- Religion in nineteenth-century America / Grant Wacker. Prophets for a new nation ; Awakeners of the heart ; Reformers and visionaries ; Restorers of ancient ways ; Sojourners at home ; Warriors for God and religion ; Fashioners of immigrant faith ; Conservers of tradition ; Adventurers of the Spirit -- Religion in twentieth- and twenty-first-century America / Randall Balmer. A new century ; The age of militancy In God we trust ; Religion in the new frontier -- Religion in an age of upheaval ; Preachers, politicians, and prodigals ; Coming to terms with pluralism ; Religion in the new millennium.
Includes bibliographical references (pages 468-496) and index.
Keywords: United States -- Religion